A Highly Efficient Metal‐Free Electrocatalyst of F‐Doped Porous Carbon toward N2 Electroreduction. Issue 24 (29th April 2020) - Liu, Yan; Li, Qiuyao; Guo, Xu; Kong, Xiangdong; Ke, Jingwen; Chi, Mingfang; Li, Qunxiang; Geng, Zhigang; Zeng, Jie
Abstract: N2 electroreduction into NH3 represents an attractive prospect for N2 utilization. Nevertheless, this process suffers from low Faraday efficiency (FE) and yield rate for NH3 . In this work, a highly efficient metal‐free catalyst is developed by introducing F atoms into a 3D porous carbon framework (F‐doped carbon) toward N2 electroreduction. At −0.2 V versus reversible hydrogen electrode (RHE), the F‐doped carbon achieves the highest FE of 54.8% for NH3, which is 3.0 times as high as that (18.3%) of pristine carbon frameworks. Notably, at −0.3 V versus RHE, the yield rate of F‐doped carbon for NH3 reaches 197.7 µgNH3 mg −1 cat. h −1 . Such a value is more than one order of magnitude higher than those of other metal‐free electrocatalysts under the near‐ambient conditions for NH3 product to date. Mechanistic studies reveal that the improved performance in N2 electroreduction for F‐doped carbon originates from the enhanced binding strength of N2 and the facilitated dissociation of N2 into *N2 H. F bonding to C atom creates a Lewis acid site due to the different electronegativity between the F and C atoms. As such, the repulsive interaction between the Lewis acid site and proton H suppresses the activity of H2 evolution reaction, thus enhancing the selectivity of N2 electroreduction into NH3 . Abstract : A F‐doped 3D porous carbon framework (F‐doped carbon) is developed as a highly efficient metal‐free catalyst toward N2 electroreduction. At −0.3 V versus reversible hydrogen electrode (RHE), the F‐doped carbon achieves a yield rate of 197.7 µgNH3 mg −1 cat. h −1 for NH3, which is more than one order of magnitude higher than those of the reported metal‐free electrocatalysts to date.